DEVELOPMENT OF ONLINE BUSINESS MATERIALS FOR SCRATCH-BASED LEARNING IN VOCATIONAL SCHOOLS - Kesumadina, Anita; Faslah, Roni; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to analyze the development of Scratch-based learning media in online business subjects in class XI Retail Business (BRI) 2 SMK Tamansiswa 1 Jakarta and analyze the validity of the Scratch-based learning media that has been developed. The research method used by the researcher is Research and Development (R&D) only up to Level 3, at this level the researcher develops existing products, research and development at level 3 is the researcher tests the product in order to develop existing products. The development model used is ADDIE which is modified according to the needs of the researcher into Analysis, Design, Development, and Implementation. The results of the media expert validation analysis obtained a percentage of 72% included in the valid category. Further validation by material experts produced a score of 60% which fell into the fairly valid validity category. The results of the questionnaire assessment given to educators showed a level of achievement reaching 78% which fell into the valid category. Based on the validity results obtained, the Scratch-based online business material learning media is included in the valid category and is suitable for use as a learning medium in the student learning process.